2004
DOI: 10.1097/01.olq.0000143107.06988.ea
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Risk Among Brothel-Based Female Sex Workers in China: Assessing the Terms, Content, and Knowledge of Sex Work

Abstract: HIV prevention activities in China must focus on sociocultural aspects of sex work. Such interventions depend on detailed knowledge of its organization. The results of this study demonstrate the importance of prevention activities directed at the brothel managers and clients, as well as the sex workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
181
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(192 citation statements)
references
References 20 publications
10
181
1
Order By: Relevance
“…According to the China public security agencies, there are an estimated 4 million female sex workers (FSWs) in China, 16 although many public health experts believe that the actual number could reach 10 million. 17 The National STD Surveillance System indicated that the majority of STIs were acquired through extramarital sex, including commercial sex.…”
mentioning
confidence: 99%
“…According to the China public security agencies, there are an estimated 4 million female sex workers (FSWs) in China, 16 although many public health experts believe that the actual number could reach 10 million. 17 The National STD Surveillance System indicated that the majority of STIs were acquired through extramarital sex, including commercial sex.…”
mentioning
confidence: 99%
“…Eligible individuals were assessed by the local investigators for study eligibility at sex venues and interviewed by the same investigators for collecting sociodemographic and behavioral data. Sex worker typologies were defined based on a modification of earlier anthropological analyses of Chinese sex workers [16]. In this study, FSWs were categorized into 3 tiers according to the venues where they solicited clients.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…This widely cited estimate lies approximately in the middle of a range of estimates of 1 to 10 million female sex workers in China (Huang et al 2004;Schafer 2003;Yuan et al 2002). In our model, female prostitutes are found in both urban (cities and towns) and rural areas (counties), consistent with evidence from numerous studies of female sex workers that suggest the widespread availability of commercial sex across urban and rural China (Hong and Li 2007;Wang et al 2009).…”
Section: Demographic Inputs (Table 1)mentioning
confidence: 99%
“…The broader width of our simulated age range of female prostitutes is informed by recent studies which employed sampling approaches intended to reach the most hidden pockets of this population who are not establishment-based (e.g. road-side sex workers) and whose age is as high as the upper thirties and early forties (Huang et al 2004;Ding et al 2005;Merli et al 2008). …”
Section: Demographic Inputs (Table 1)mentioning
confidence: 99%